Analyzing the Digital Entrepreneurship Academy of Ministry of Communication and Information Surabaya in Pamekasan - Sandika Rhamadona; Siska Sufa; Meithiana Indrasari; Garry Brumadyadisty; Anita Asnawi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
The Digital Talent Scholarship (DTS) program by the Ministry of Communication and Information Technology (Kominfo) aims to enhance the skills and competencies of Indonesian human resources in the digital field. One such program is the Digital Entrepreneurship Academy (DEA) program, which trains individuals to accelerate the growth of digital technology in entrepreneurship. This study aims to understand the DEA Program training in Pamekasan Regency, conducted by BPSDMP Kominfo Surabaya, and its benefits. The qualitative research method used is interviews, observation, documentation, and literature studies. Results show that almost 100% of participants in the DEA program experienced success in business development through networking both offline and online. The study concludes that progress has been significant in the DEA Program training, particularly during the COVID-19 pandemic, which has shifted many activities from conventional to digital, including entrepreneurial activities. Monitoring is necessary to ensure the program's resources, expected outputs, and constraints. The research aims to provide an overview and study of digital entrepreneurship by the government to the community.